Shame/Honor, Guilt/Innocence, Fear/Power in Relationship Contexts - Beech, Geoff (International bulletin of mission research, 2018)
All human beings seek to avoid shame, guilt, and fear, responses that sociologists have paired, respectively, with honor, innocence, and power. Examination of cultures has shown that the shame/honor, guilt/innocence, and fear/power affective domain pairs are prioritized differently in different cultures. Western missiologists have seen the connection between guilt and innocence and the Gospel but have also shown interest in the other pairs, and some have linked pair prioritization with particular religious contexts. My research found that, rather than religion per se, the prioritizations emerge from deeply embedded worldview assumptions pertaining to relationship structures, which are culturally or socially determined.